(untitled) (XXI Century. Spanish Literature and Culture, 2004)
A thoughtful essay of the author on what or who decides the imposition of Spanish as the language of literature in Spain above Catalan or any of the other languages spoken in the country, with a retrospective outlook of her childhood as a nest for her current opinion, which holds that every author chooses the language in which it feels more natural and fluid to communicate with their readers.